2015
DOI: 10.4103/2152-7806.153645
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening posterior fossa cyst induced by pseudomeningocele after operation for acoustic neuroma

Abstract: Background:Pseudomeningocele is the term used to describe fluid accumulation due to the leakage of cerebrospinal fluid into the surrounding soft tissue. It may cause complications such as cosmetic deformities, chronic meningitis, and/or impingement on vital structures resulting in neurological deficits; nevertheless, life-threatening posterior fossa cyst formation is a rare event.Case Description:We report a case of posterior fossa cyst formation induced by pseudomeningocele with brain stem compression leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…These reports, similarly to ours, concluded that dural defects and small tears in the arachnoid and parenchyma of the cerebellum affect the one-way valve mechanism, causing CSF to accumulate in the cyst. 3,4,8,9 This emphasizes the CSF connection between the pseudomeningocele and the cyst, similar to our case.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These reports, similarly to ours, concluded that dural defects and small tears in the arachnoid and parenchyma of the cerebellum affect the one-way valve mechanism, causing CSF to accumulate in the cyst. 3,4,8,9 This emphasizes the CSF connection between the pseudomeningocele and the cyst, similar to our case.…”
Section: Discussionsupporting
confidence: 89%
“…7 In our case, pseudomeningocele occurred postoperatively, a rare event since postoperative incidence is reported as 4.5% after neurological procedures. 3 These lesions are primarily occipital, with few supratentorial lesions reported. Pseudomeningocele formation is mainly from inadequate closure of the dura mater 8 that allows extradural accumulation of CSF and cystic enlargement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 2 3 4 5 6 ] Besides inducing anxiety to patients and their families, these lesions may cause cosmetic deformity, wound dehiscence, CSF leak, intracranial hypotension, aseptic meningitis, and even death. [ 7 8 ] Hydrocephalus, poor surgical closure of the dura, and subarachnoid scarring have all been implicated as potential contributing factors. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%